2007
DOI: 10.1002/cne.21472
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Aminobutyric acid (GABA) signaling components in Drosophila: Immunocytochemical localization of GABAB receptors in relation to the GABAA receptor subunit RDL and a vesicular GABA transporter

Abstract: gamma-Aminobutyric acid (GABA) is a major inhibitory neurotransmitter in insects and is widely distributed in the central nervous system (CNS). GABA acts on ion channel receptors (GABA(A)R) for fast inhibitory transmission and on G-protein-coupled ones (GABA(B)R) for slow and modulatory action. We used immunocytochemistry to map GABA(B)R sites in the Drosophila CNS and compared the distribution with that of the GABA(A)R subunit RDL. To identify GABAergic synapses, we raised an antiserum to the vesicular GABA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 52 publications
11
98
0
1
Order By: Relevance
“…Previous studies have shown that there are large numbers of GABA-producing neurons in the adult brain of Drosophila (Enell et al, 2007;Okada et al, 2009). The processes of some of these arborise in the region of the accessory medulla that contains presumed dendrites of the PDF neurons (Hamasaka et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that there are large numbers of GABA-producing neurons in the adult brain of Drosophila (Enell et al, 2007;Okada et al, 2009). The processes of some of these arborise in the region of the accessory medulla that contains presumed dendrites of the PDF neurons (Hamasaka et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In western blots of brain tissue from Drosophila the antiserum detected a band of appropriate size (Hamasaka et al, 2005), and in GABA B -R2 immunohistochemistry on Drosophila brains the antiserum labelled neurons that were in close proximity to neural elements immunopositive for a vesicular GABA transporter, GAD and a GABA A receptor (RDL), strongly indicating that the GABA B -R2 antiserum is reliably detecting a GABA B receptor (Enell et al, 2007). The anti-GABA B -R2 specificity was further established by diminished GABA B -R2 immunolabelling after GABA B -R2 RNAi in specific neurons (OSNs) in the antenna/antennal lobe (Root et al, 2008).…”
Section: Gaba B -R2 Antiserummentioning
confidence: 98%
See 1 more Smart Citation
“…In larger fly species (Strausfeld and Bassemir, 1983;Heisenberg and Wolf, 1984), electron microscopical observations confirm that these Col A-GDN synapses are monosynaptic, comprising mixed chemical and electrical junctions. If the chemical synapses between Col A neurons and the GDN are excitatory (Enell et al, 2007;Strausfeld et al, 2007), inhibitory response seen in the GDN to some light-on stimuli are likely to derive from a separate neural pathway. Pathways carrying information about light-on and light-off may indeed be interdependent because the intensity of response to light-off is related to the prior duration of light-on.…”
Section: Discussion Neural Pathways Mediating Visual Inputs To the Gdnmentioning
confidence: 99%
“…In Drosophila MBs, the GABA A receptor subunit RDL is expressed throughout the substructures except the cell body area (Liu et al, 2007), whereas the GABA B receptor R2 (GABA B -R2) subunit is expressed only in calyx (Enell et al, 2007). Of the various MB Gal4 lines, we focused our attention principally on the 17d-Gal4 (Fig.…”
Section: The Apl Neurons Are Required For Visual Reversal Learningmentioning
confidence: 99%